2018
DOI: 10.4314/mmj.v30i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the quality of care in Maternity Waiting Homes (MWHs) in Mulanje District, Malawi

Abstract: AimMaternal Mortality Ratio (MMR)in Malawi remains high at 439 deaths per 100,000 live births, primarily due to limited access to skilled birth care. Although Malawi established Maternity Waiting Homes (MWHs) to improve access to skilled labour, the quality of care provided in the homes has received limited assessment. The aim of this study was to assess quality of care in the Maternity Waiting Homes in Mulanje, Malawi. MethodsWe conducted a descriptive qualitative study in three MWHs in Mulanje district, Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…The provision of food at MWHs was heterogeneous. A study from Ethiopia reported that more than half of MWH users responded food was not affordable while staying at MWH [ 16 ] which was consistent with the findings from the studies in different countries found that the availability of food was the main reason women agreed or chose to use a MWH [ 15 , 17 - 20 ] or a barrier for MWH utilization [ 6 , 21 ].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The provision of food at MWHs was heterogeneous. A study from Ethiopia reported that more than half of MWH users responded food was not affordable while staying at MWH [ 16 ] which was consistent with the findings from the studies in different countries found that the availability of food was the main reason women agreed or chose to use a MWH [ 15 , 17 - 20 ] or a barrier for MWH utilization [ 6 , 21 ].…”
Section: Discussionsupporting
confidence: 64%
“…The similarity might be due to the MWHs sharing resources with the health facilities. A Zambian study reported that the majority of MWH users had access to water, electricity and a toilet [ 14 ], but as study from Malawi reported that MWH users could not access reliable water or electricity [ 15 ]. The provision of food at MWHs was heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…MWH users perceived MWHs as a resting place, where women could take a break from their household and domestic tasks, which was perceived as beneficial before giving birth [ 13 , 23 , 38 – 41 , 45 , 48 , 49 ]. All subgroups felt they had easier access to health services when using the MWH, including better monitoring by health staff and easier transfer to higher-level facilities when complications occurred [ 7 , 12 , 19 , 24 , 35 , 37 , 39 , 41 , 42 , 50 – 53 ]. Other incentives for MWH users were health education [ 34 , 49 , 54 ], free lodging [ 13 , 39 ], the possibility of avoiding negative experience with home births [ 37 , 43 ], the benefits of sharing experiences and doing tasks together with other women [ 23 , 38 , 40 , 41 , 46 , 50 , 55 ] and the possibility of learning a new skill, such as sewing or gardening [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Medical doctors were in short supply in the MoH and most clinical care was provided by clinical officers and clinical technicians, para-medical staff holding 4-year medical degrees or 3-year diplomas, respectively (Jiskoot, 2008;van Amelsfoort et al, 2010), or nurse-midwives. To promote facility births, maternity wards in district hospitals and some health centers also functioned as waiting homes, with expectant mothers admitted up to 1 month prior to their estimated delivery dates (Singh et al, 2018;Suwedi-Kapesa & Nyondo-Mipando, 2018).…”
Section: Health Care In the Republic Of Malawimentioning
confidence: 99%